Hydrogeochemical analysis and paleo-hydrogeological modeling of shallow groundwater salinization processes in North China Plain - Huang, Yihong; Yang, Jie; Yu, Xuan; Wang, Shijie; Xie, Xianjun; Li, Junxia; Wang, Yanxin (Journal of hydrology (Amsterdam), 2025)
•Shallow groundwater salinization was resulted from the several events of marine transgression.•Free convection dominated transport of groundwater salinity influenced by heterogeneous geological structure.•Downward permeation of shallow saline water introduces the salinity into deep aquifer. Coastal groundwater salinization induced by marine transgression, sea level rising, and/or seawater intrusion due to anthropogenic activities has been a challenge for water security worldwide. Understanding of the spatial distribution of saline water and its sources is important for the protection of fresh groundwater resources from salinization necessitates. In this study, the processes of groundwater salinization in two shallow aquifers of the North China Plain near Bohai Sea were characterized using hydrogeochemical analysis and paleo-hydrogeological modeling. The groundwater Cl in the shallow Aquifer I and II had the ranges of 10.2 ∼ 21556 mg/L and 79.1 ∼ 15800 mg/L, respectively. The distribution of groundwater isotopic signatures and chemistry, including Cl/Br molar ratio, indicates that the shallow groundwater within a distance less than ∼ 60 km to Bohai Sea is affected by the marine transgression/regressions. The groundwater in Aquifer II was more widely influenced by the saline water compared to that in Aquifer I. The results of paleo-hydrogeological modeling confirmed the primary role of several events of marine transgressions in groundwater salinization. The fingering process of vertical infiltration of saline water by free convection was identified from the modeling results, which was constrained by preferential flow paths and low permeability barriers of aquitards. The modeling results show that seawater infiltration was rapid, reaching a depth of 140–160 m B.S.L.. The trend of downward permeation of shallow saline water would further threaten the groundwater quality of shallow and deep aquifers that sever as the sources of water supply in coastal area of the North China Plain.